People with Aphasia Shape Spirituality Research: Unlocking Insights into Access and Acceptability - Mumby, Katharyn (Journal of disability & religion, 2025)
Underrepresented in research coproduction, and in spirituality research, people with aphasia partnered with the author in action research incorporating communication access techniques. They became a coproduction steering group for a study into assessing and supporting spiritual health in aphasia. The Steering group were embedded at multiple levels in the research process, likened to negotiating locks on a canal. The coproduction evidenced how published standards could be met when including people with communication disability. The process shaped the WELLHEAD Toolkit (for spiritual health assessment and support – the product) in its feasibility study, thus ensuring accessibility and acceptability from a range of spiritual and religious viewpoints. Co-creation (product and process) was valued, with impact upon spirituality of those participating as their perceptions were unlocked. Further work is exploring how far others’ perceptions of their spirituality may be unlocked using the WELLHEAD Toolkit techniques, including applications beyond speech and language therapy and communication disability, to support holistic rehabilitation and wellbeing.